Climate change and cancer: converging policies. Issue 3 (22nd September 2020) - Vineis, Paolo; Huybrechts, Inge; Millett, Christopher; Weiderpass, Elisabete
Abstract : Intervening on risk factors for noncommunicable diseases (including cancer) in industrialized countries could achieve a reduction of between 30% and 40% of premature deaths. In the meantime, the need to intervene against the threat of climate change has become obvious. CO2 emissions must be reduced by 45% by the year 2030 and to zero by 2050 according to recent agreements. We propose an approach in which interventions are designed to prevent diseases and jointly mitigate climate change, the so‐called cobenefits. The present article describes some examples of how climate change mitigation and cancer prevention could go hand in hand: tobacco control, food production, and transportation (air pollution). Many others can be identified. The advantage of the proposed approach is that both long‐term (climate) and short‐term (health) benefits can be accrued with appropriate intersectoral policies. Abstract : Many human activities cause a double burden, on health and on the environment. A few examples are as follows: Air pollution causes greenhouse gas emissions and several human diseases (left). Food production and trades are involved in loss of biodiversity, greenhouse gas emissions, and human diseases such as zoonoses or excess cancer and cardiovascular diseases (right). Intersectoral policies can contribute to the achievement of several Sustainable Development Goals.